Messverfahren zur objektiven Beurteilung der nasalen Durchgängigkeit - Giotakis, Aristeidis I.; Vent, Julia (Laryngo-Rhino-Otologie, 2019)
The need for objective assessment of nasal patency in the fields of rhinosurgery and allergy has led to the development of various methods for the evaluation of nasal patency. These methods include active anterior rhinomanometry, PNIF, acoustic rhinometry, rhinostereometry, optical rhinometry, minimal cross-sectional area endoscopy, nasal sound spectral analysis, magnetic resonance imaging and numerical flow simulation. This article provides a brief overview of currently common procedures.
Gesehen am 20.08.2019